EPIGRAPHIC ANALYSIS OF TOMBSTONES OF BALKAR ARISTOCRATS IN VERKHNY CHEGEM CEMETERY AND THEIR BIOGRAPHICAL DETAILS - Barazbiev, Muslim Ismailovic; Bogatyrev, Aslan Alievic (History, Archeology and Ethnography of the Caucasus, 2025)
The ancient Balkar village of Eltyubyu, also known as Verkhny Chegem, is situated in the upper reaches of the Chegem River in the southwestern part of the Chegem District, Kabardino-Balkarian Republic. Prior to the October Revolution, Verkhny Chegem served as the central settlement of the Chegem Society of Balkaria, hosting members of all its princely families. This study examines Arabic-language tombstones of Balkar aristocrats located in the cemetery of Eltyubyu (Verkhny Chegem) and provides biographical data on the individuals commemorated. The significance of this research stems from its novelty, as the topic has not been the subject of dedicated academic research, offering new insights into the social history and ethnography of the Balkar people. The surviving epitaphs on these tombstones represent a valuable historical source, particularly in light of the tragic events that impacted the Balkar aristocracy in the 20th century. The objective of this study is to translate the Arabic inscriptions on the tombstones of the Chegem princes and to provide concise biographical details about them. An interdisciplinary approach was adopted, incorporating narrative, historical-genealogical, and contextual methodologies. The translations of epitaphs from ten tombstones, identified by the authors, are introduced into academic discourse for the first time. Notably, the names of stone carvers were identified on some of the tombstones, adding to their scholarly value. The tombstones belong to members of the principal aristocratic families of the Chegem Society of Balkaria, namely the Balkarukovs, Barasbievs, and Kelemetovs, with the exception of the Kuchukovs, who remain unidentified at this stage. The content of the epitaphs from the Eltyubyu (Verkhny Chegem) cemetery enhances our understanding of the genealogy of the Balkar aristocracy and contributes significantly to the broader historical and cultural knowledge of the Balkar people.
Keywords: Balkaria; Chegem society; cemetery; epitaph; stele; biography; aristocracy; document